Implementasi Penarikan Royalti Pengguna Lagu/Musik Pada Usaha Mikro, Kecil, Kafe di Kota Samarinda - Gunawan, Andi Lolo; Kuspraningrum, Emilda; Hediati, Febri Noor (Jurnal Suara Hukum, 2023)
Song/Music users who use songs for commercial purposes are required to pay royalties after the issuance of Government Regulation Number 56 of 2021 concerning Management of Royalties for Copyright of Songs/Music. The problems studied in this study are how the regulation of the withdrawal of royalties for song/music users in micro, small cafes and how the implementation of the regulation of the withdrawal of royalties for song/music users in micro, small businesses in Samarinda City. This research uses a sosio legal research. The results showed that first, Government Regulation Number 56 of 2021 concerning Management of Royalties for Copyright of Songs/Music regulates the obligation to pay royalties and the institution authorized to collect royalties for songs/music, namely the National Collective Music Management Institute (LMKN), then also regulates payment relief for business actors with the Micro Business category. But there is no sanction regulation explicitly stipulated in Government Regulation No. 56 of 2021 for song/music users who use songs/music for commercial purposes illegally. Second, awareness of the obligations and how to pay song and/or music royalties is still low even though the National Collective Management Institute (LMKN) has conducted socialization about song/music royalties. The absence of the Song and Music Information System (SILM) makes the National Collective Management Institute (LMKN) set a priority scale in collecting song/music royalties to commercial users of songs/music with the priority of large and medium users, for users with small National Collective Management Institution (LMKN) has not been able to reach because it requires large operational costs.